The adjunctive effect for left pulmonary vein isolation of vein of Marshall ethanol infusion in persistent atrial fibrillation. Issue 2 (12th December 2022) - Huang, Lihong; Gao, Mingyang; Lai, Yiwei; Guo, Qi; Li, Songnan; Li, Changyi; Liu, Nian; Wang, Wei; Liu, Xiaoxia; Zuo, Song; Guo, Xueyuan; Zhao, Xin; et al.
Abstract: Objective: This study sought to assess the effect of ethanol infusion into the vein of Marshall (EIVOM) on the acute success of left pulmonary vein (LPV) isolation in persistent atrial fibrillation (PeAF). Methods and results: A total of 313 patients with drug-resistant PeAF were enrolled (135 in Group 1 and 178 in Group 2). In Group 1, EIVOM was firstly performed, followed by radiofrequency ablation (RFA) including bilateral pulmonary vein isolation (PVI) and linear ablation at roofline, cavotricuspid isthmus, and mitral isthmus (MI). In Group 2, PVI and linear ablations were completed with RFA. First-pass isolation of the LPV was achieved in 119 (88.1%) and 132 (74.2%) patients in Groups 1 and 2, respectively ( P = 0.002). The rate of acute pulmonary vein reconnection (PVR) was significantly lower in Group 1 (9.6% vs. 22.5%, P = 0.003). About half of acute PVR occurred in the carina with or without EIVOM. Conclusion: EIVOM is effective in achieving a higher first-pass isolation and a lower acute PVR of LPV in PeAF.